Revisiting the ultraluminous supersoft source in M 101: An optically thick outflow model - Soria, Roberto; Kong, A. (Oxford University Press, 2016)
The M 101 galaxy contains the best-known example of an ultraluminous supersoft source (ULS), dominated by a thermal component at kT ≈ 0.1 keV. The origin of the thermal component and the relation between ULSs and standard (broad-band spectrum) ultraluminous X-ray sources are still controversial. We re-examined the X-ray spectral and timing properties of the M 101 ULS using archival Chandra and XMM–Newton observations. We show that the X-ray time-variability and spectral properties are inconsistent with standard-disc emission. The characteristic radius Rbb of the thermal emitter varies from epoch to epoch between ≈10 000 and ≈100 000 km; the colour temperature kTbb varies between ≈50 and ≈140 eV and the two quantities scale approximately as R bb ∝T −2 bb Rbb∝Tbb−2. In addition to the smooth continuum, we also find (at some epochs) spectral residuals well fitted with thermal-plasma models and absorption edges: we interpret this as evidence that we are looking at a clumpy, multitemperature outflow. We suggest that at sufficiently high accretion rates and inclination angles, the supercritical, radiatively driven outflow becomes effectively optically thick and completely thermalizes the harder X-ray photons from the inner part of the inflow, removing the hard spectral tail. We develop a simple, spherically symmetric outflow model and show that it is consistent with the observed temperatures, radii and luminosities. A larger, cooler photosphere shifts the emission peak into the far-UV and makes the source dimmer in X-rays but possibly ultraluminous in the UV. We compare our results and interpretation with those of Liu et al.